The Impact of an Introductory Biomedical Engineering Course on Students' Perceptions of the Engineering Profession (2016)
After their ﬁrst year roughly 50% of engineering students do not continue in that major. One cause could be that students have little idea as to what the profession of engineeringis about. Freshman introductory courses provide a ﬁrst approach to the engineering profession. Therefore, understanding the role of introductory engineering courses to increasing student knowledge of the profession is a relevant issue. The purpose of the study is to describe how student perceptions of the engineering profession overall change as a result of their educational experience in an introductory biomedical engineering course.This is a pre-post-test with no control group study design.One class(n =41)on a ﬁrst-year biomedical engineering course participated in a hybrid Project-based-learning (PBL)-lecture learning strategy. A survey composed of a demographic and 5-point Likert (‘‘1’’ is strongly disagree and ‘‘5’’ is strongly agree) sections measured students’ perceptions of the engineering profession and was administered (paper-based) to all the students enrolled on this course. The students’ perceptions of the engineering profession were pooled into 3 main groups of skills, i.e. Technical skills, Professional skills, and Project management skills. Wilcoxon signed-rank test statistics were conducted to analyze the research question. Our analysis showed statistically signiﬁcant results (pre-survey mean and SD: 4.01, 0.07; and post-survey mean and SD: 4.21, 0.05, p < 0.003), indicating the students’ overall perceptions of the engineering profession had signiﬁcantly improved by the end of the course. The results indicated that the students’ overall perceptions of the engineering profession had signiﬁcantly improved by the end of the introductory course.